Optimizing Students’ Communication Skills through Kahoot-Assisted Project Based Learning in Biology Learning - Sonia Sumiarti Gurning; Miswandi Tendrita; Erfina Erfina; Sutriani Kaliu (JURNAL PEMBELAJARAN DAN BIOLOGI NUKLEUS, 2026)
Background: Preliminary observations at SMAN 1 Wundulako Senior High School indicated that students had limited communication skills during biology learning because classroom instruction tended to be teacher-centered and provided insufficient opportunities for active interaction. Therefore, an innovative learning model such as Project-Based Learning supported by Kahoot is needed to enhance student engagement and optimally develop communication skills. Methodology: This research adopted a quantitative approach through a quasi-experimental method employing a posttest-only control group design. The participants consisted of 60 tenth-grade students at SMAN 1 Wundulako, with one class assigned as the experimental group and the other as the control group. Data were collected using a communication skills observation sheet, content-validated by two experts, measuring four indicators expressing and responding to opinions, mastery of presentation material, presenting findings clearly and systematically, and language use. Data were analyzed using an independent-samples t-test at a significance level of 0.05. Findings: Kahoot was integrated into the Project-Based Learning process as an interactive formative assessment tool. The findings demonstrate that PjBL integrated with Kahoot produced a statistically significant improvement in students' communication skills (p < 0.05), with the experimental group achieving a higher mean score (89.37) than the control group (50.83). Contribution: This learning model is capable of enhancing communication skills through collaborative activities, project presentations, and interactive quiz-based interactions. Thus, PjBL supported by Kahoot is effective as an innovative learning alternative for improving students’ communication skills. This study contributes to biology education by providing empirical evidence that integrating Kahoot into Project-Based Learning offers an effective technology-supported strategy for enhancing communication skills in senior high school biology classrooms